Bottom-up synthesis of graphene via hydrothermal cathodic reduction. (March 2020) - Tomai, Takaaki; Nakayasu, Yuta; Okamura, Yusuke; Ishiguro, Shunichi; Tamura, Naoki; Katahira, Shusuke; Honma, Itaru
Abstract: To date, considerable effort had been devoted to developing a bottom-up synthesis method of graphene, but the methods have been mostly limited to chemical vapor deposition and SiC surface decomposition. Herein, we demonstrated the bottom-up synthesis of graphene via hydrothermal cathodic reduction. In the developed process, the hydrothermal conditions were tuned to enhance the electrochemical reaction and prevent the formation of undesirable amorphous carbon. The nature of the deposited carbonaceous material depends strongly on the temperature, and changes from amorphous carbon into graphitic carbon and graphene with increasing temperature. This should be because of the enhanced oxidative etching effect of amorphous carbon under hydrothermal condition. Finally, the hydrothermal electrochemical reaction enabled graphene growth on a cathode surface at 300 °C. Graphical abstract: Image 1